Соціальна реклама як тематика творчої роботи на олімпіаді з web-технологій та web-дизайну - Глібко, Олена Анатоліївна; Сімонова, Ольга Геннадіївна; Савченко, Л. М. (Полтавський національний технічний університет ім. Юрія Кондратюка, 2017)
Стаття присвячена аналізу досвіду проведення 1 туру Всеукраїнської олімпіади студентів з web-технології і web-дизайну, створенню промо-сайту про день відкритих дверей НТУ "ХПІ", розкриттю ролі соціальної реклами у підвищенні серед абітурієнтів мотивації до вступу у виш.

The article is devoted to the analysis of the experience of conducting the 1st round of the All-Ukrainian Olympiad of students on web-technology and web-design, creation of a promo-site about the day of the open doors of NTU "KhPI" to reveal the role of social advertising in raising among the entrants of motivation to enter higher education institutions.
Social advertising as a thematic of creative work on olympiad with web technologies and web design
Keywords: промо-сайт; творчі завдання; веб сайт; дизайн сайту; promo-site; creative tasks; means of web-layout; social advertising